2016
DOI: 10.18632/oncotarget.12864
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variant in visfatin gene promoter contributes to reduced risk of hepatocellular carcinoma in a Chinese population

Abstract: Knowledge on the role of gene variants in the visfatin promoter region in the hepatitis B virus (HBV)-related liver diseases is limited. In this study, we genotyped two potentially functional single nucleotide polymorphisms (SNPs) in the visfatin promoter region, -1535C>T (rs61330082) and -3187G>A (rs11977021), in 120 HBV-related chronic hepatitis B (CHB) patients, 140 HBV-related liver cirrhosis (HBV-LC) patients, 243 HBV-related hepatocellular carcinoma (HBV-HCC) patients, and 224 asymptomatic HBV carriers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Previous research has reported visfatin rs11977021 frequencies for CC, CT and TT genotypes among controls of 23.2%, 54.5% and 22.3%, respectively, and corresponding visfatin rs61330082 frequencies for CC, CT and TT genotypes among controls of 39.7%, 45.1% and 15.2%, respectively 17 . Another publication has reported visfatin rs2110385 frequencies for GG, GT and TT genotypes among controls of 75.6%, 24.4% and 0%, respectively (NCBI dbSNP HapMap-HCB population), and visfatin rs4730153 frequencies for GG, GA and AA genotypes among controls of 84.1%, 15.9% and 0%, respectively 28 .…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous research has reported visfatin rs11977021 frequencies for CC, CT and TT genotypes among controls of 23.2%, 54.5% and 22.3%, respectively, and corresponding visfatin rs61330082 frequencies for CC, CT and TT genotypes among controls of 39.7%, 45.1% and 15.2%, respectively 17 . Another publication has reported visfatin rs2110385 frequencies for GG, GT and TT genotypes among controls of 75.6%, 24.4% and 0%, respectively (NCBI dbSNP HapMap-HCB population), and visfatin rs4730153 frequencies for GG, GA and AA genotypes among controls of 84.1%, 15.9% and 0%, respectively 28 .…”
Section: Methodsmentioning
confidence: 94%
“…Visfatin single-nucleotide polymorphisms (SNPs) rs11977021, rs61330082, rs2110385 and rs4730153 were chosen on the basis of prior research showing that they increased the risk of various cancers 14 , 17 - 19 . All SNPs had minor allele frequencies exceeding 5%.…”
Section: Methodsmentioning
confidence: 99%
“…The infections of HBV and HCV are major reasons for HCC onset, with the former one as the leading cause in China. [13] Five-year survival rate of patients with HCC is reportedly <10%. [14] Biomarkers are beneficial to early diagnosis, prognosis evaluation, and treatment in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Increased visfatin is associated with a poor prognosis in patients with HCC [226,227], which is underlined by its association with HCC progression [228]. Significantly increased visfatin expressions were also seen in patients with liver cirrhosis compared to controls [227].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%